Lian (PSB Rc 98), a new rainfed-lowland rice variety - Rice Variental Improvement Program Team (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2003)
Lian (PSB Rc 98) is a rainfed-lowland rice variety released by the National Seed Industry Council (NSIC) in 2001. In advanced yield trials conducted in five locations, it had an average yield advantage of 6% over the check variety PSB Rc 14 in drought-prone environments and 27.6% and 7.4% over PSB Rc 38 and PSB Rc 40 in 5 additional locations, respectively, during the wet season trials. Lian matures in 116 d and grows to a height of 98 cm. Its high yield potential was also exhibited in technology promotion trials conducted in farmers' fields during the 1998 and 1999 wet seasons.